Oil price and stock market returns uncertainties and private investment in Saudi Arabia - Imed Medhioub; Mohammed Makni (Economic Journal of Emerging Markets, 2020)
The private sector plays a crucial role in the economy. This paper constructs an empirical model for the sector in Saudi Arabia. It incorporates oil price uncertainty as well as stock market returns volatility to predict the sector. It estimates the GARCH (generalized autoregressive conditional heteroskedasticity) and ARDL (autoregressive distributed lag) models. Findings/Originality: Our estimations show significant evidence of a long-run relationship between private investment, oil price, and the stock market. We also find that the stock market index has a significant positive effect on private investment in the short run. The effects are strong in the case of unexpected news from the oil sector. Oil price uncertainty can be considered as a channel of transmission of negative shocks on the private sector. For these reasons, when Saudi Arabia has launched its 2030 vision, it announced that one of its goals is to become a non-oil dependent country.